Analgesic management of uncomplicated acute sickle-cell pain crisis in pediatrics: a systematic review and meta-analysis - Manou Irmina Saramba; Sandeep Shakya; Dongchi Zhao (Elsevier, 2020)
Objectives: To capture evidence of the efficacy and safety of pharmacological analgesia for uncomplicated acute sickle-cell pain in pediatric patients compared to placebo. Sources of data: Searches for key evidence were performed from March 1 to 31, 2018, for randomized controlled trials of pharmacological analgesia compared to placebo for uncomplicated acute sickle-cell pain in a pediatric sample. The authors searched ten scientific databases including, among others, PubMed, MEDLINE, Embase, and Clinicaltrials.gov for this systematic review and meta-analysis. Summary of the findings: Four trials (n = 227) were selected by the inclusion criteria (intranasal fentanyl, intravenous magnesium, arginine, and inhaled nitric oxide). The quality of evidence ranged from low to moderate for each outcome. Meta-analysis of changes in the ladder of pain score (p = 0.72), length-of-stay in hospital (p = 0.65), and amount of narcotics used during the study (p = 0.10) showed non-statistically significant differences and a lack of amelioration provided by pharmaceutical analgesics in treatment group. The adverse events reported that more participants in the intervention arm underwent pain, with statistically significant differences at the drug delivery site in studies using intranasal fentanyl and intravenous magnesium (p = 0.03). Conclusions: Pharmacological analgesia appears to be uncertain in improving the intensity and providing relief of acute pain crisis in pediatric patients with sickle-cell anemia. With respect to clinical advantage, no decisive deduction about the clinical efficacy may be made regarding these medications in acute sickle-cell pain management in the pediatric age group. Resumo: Objetivos: Obter evidências da eficácia e segurança da analgesia farmacológica para dor falciforme aguda não complicada em pacientes pediátricos em comparação com placebo. Fontes de dados: Uma busca de evidências-chave foi feita de 1º a 31 de março de 2018 por ensaios clínicos randomizados controlados de analgesia farmacológica em comparação com placebo para dor aguda falciforme não complicada em uma amostra de pacientes pediátricos. Os autores pesquisaram dez bases de dados científicos que envolveram, entre outras, PubMed, Medline, Embase e Clinicaltrials.gov para esta revisão sistemática e metanálise. Resumo dos dados: Quatro ensaios (n = 227) foram considerados para critérios de inclusão (fentanil intranasal, magnésio intravenoso, arginina e óxido nítrico inalado). As evidências de qualidade variaram de baixas a moderadas para cada desfecho. A metanálise de alterações na escala de dor (p = 0,72), o tempo de internação hospitalar (p = 0,65) e a quantidade de analgésicos usados durante o estudo (p = 0,10) mostraram diferença não estatisticamente significativa e a ausência de melhoria resultante do uso do fármaco analgésico no grupo de tratamento. Os eventos adversos relatados mostraram que no braço de intervenção mais participantes sofreram dor com diferença estatisticamente significativa no local de aplicação do fármaco com o uso de fentanil intranasal e magnésio intravenoso (p = 0,03). Conclusões: A analgesia farmacológica parece ter um efeito incerto na melhoria da intensidade e alívio da crise de dor aguda em pacientes pediátricos com doença falciforme. Em relação à vantagem clínica, ainda é incerta a eficácia clínica desses medicamentos no tratamento da dor aguda falciforme no grupo etário pediátrico. Keywords: Anemia, sickle cell, Sickle cell disease, Acute pain, Analgesic drugs, Pediatrics, Palavras-chave: Anemia falciforme, Doença falciforme, Dor aguda, Drogas analgésicas, Pediatria